Identification and expression analysis of MicroRNAs in chicken spleen in a corticosterone-induced stress model. (May 2021) - Su, Aru; Zhou, Yanting; Guo, Yujie; Yang, Xiuling; Zhang, Yanhua; Li, Wenting; Tian, Yadong; Li, Kui; Sun, Guirong; Jiang, Ruirui; Han, Ruili; Kang, Xiangtao; et al.
Abstract: For investigating the effects of stress on the immune response of chickens, we established a corticosterone (CORT)-induced stress model by exogenous intake of CORT. Control group was fed with a basal diet and the stress model group was fed with a 30 mg/Kg CORT-treated diet in ad libitum conditions for 7 days. Then, we used RNA-seq technology to identify the expression pattern of miRNAs, target genes, and relevant pathways in chicken spleen. Results showed that 71 differentially expressed miRNAs (DEMs) were determined, 9 of which were significantly differentially expressed miRNAs (SDEMs), and 241 target genes of DEMs were predicted. GO annotation and KEGG pathway analysis were carried out to understand the role of the DEMs. Out of 287 significantly enriched GO terms, 37 were stress- or immune-related, such as response to light stimulus, detection of oxidative stress, and immune response in mucosal-associated lymphoid tissue. Out of 85 KEGG pathways, 8 were related to stress or immunity, such as cytokine-cytokine receptor interaction, JAK-STAT signaling pathway, and RLR signaling pathway. We then constructed the interaction networks between target genes from immune-related pathways and their DEMs. The analysis results suggested that some DEMs (gga-miR-17 family, gga-miR-15/16 family, gga-miR-2954 and gga-miR-34b-5p) and target genes ( SIKE1, CX3CL1, IL11Ra, PIGR, and CDKN1A ) were core miRNAs and genes. This study revealed the dynamic miRNA transcriptome, target genes and related pathways in chicken spleen under CORT-induced stress model, which provided a basis for studying the molecular mechanism of stress affecting immune function. Highlights: A corticosterone-induced stress model was constructed in Gushi chicken.. 71 differentially expressed miRNAs (DEMs) were identified by RNA-seq technology. 37 GO terms and 8 enrichment pathways of target genes were involved in stress reaction or immunity regulation. MiR-15/16 and miR-17 family and SIKE1, CX3CL1, IL11Ra were core miRNAs/mRNAs in stress-induced immunoregulation.